The impact of material hardship severity and frequency on health outcomes: Evidence from New York City - Trevor Memmott (PLoS ONE, 2025)
Material hardship – the struggle to meet basic household needs – regularly impacts millions of Americans. Despite a growing body of research on the impacts of economic deprivation, a comprehensive understanding of the ways in which the experience of material hardship impacts health is still lacking in extant literature. To address these shortcomings, this manuscript analyzes data from the NYC Poverty Tracker, a longitudinal survey designed to capture the experience of material hardship among New York City residents, to explore the relationship between five major forms of hardship (food, energy, housing, financial, and medical) and physical and mental health outcomes. Findings show a clear association between all five forms of hardship and diminished health outcomes. Further, the frequency (how often), severity, and experience of facing multiple hardship simultaneously is associated with larger negative impacts on how a respondent rates their physical and mental health. These results offer a more detailed, comparative understanding of the way material hardships intersect with health, suggesting the need for targeted policy responses that not only address immediate deprivation but also consider the broader health implications that results for those living under chronic hardship. The findings offer key insights into the literature on health and social welfare in addition to important evidence for policymakers attempting to alleviate the burden of material hardship and improve public health outcomes.